"Poker Bluff" – The European Crisis. Issue 75 (January 2015) - Das, Satyajit
Abstract : The ECB is increasingly reliant on influencing market sentiment to buy time; hoping growth, inflation and structural reforms restore the Euro‐Zone's fortunes.